Stabilization of Credit and Operation in the Coal Industry - Frank Haas (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1930)
THE public generally has-become aware that there is something wrong with the coal industry and a clamor has arisen for an explanation if not a remedy for this disorder. It is only reasonable that this Institute be looked to for a diagnosis to show the way for some other .agency to prepare the patient for prescription or operation. The subject is extensive, widely diversified, and beyond the efforts of an individual to cover completely; one of the objects of this paper is the initiating of a symposium on the non- technical factors essential to an understanding of the bituminous coal industry. The present condition of the coal industry cannot be described in a few words but, in effect, it resolves itself into a simple statement: The average coal operator is losing money notwithstanding a firm conviction on the part of the consumer that he pays too much for his coal. Without enumerating the many and varied. factors which contribute to this condition, this paper will be devoted to the interrelation of taxation and ownership of coal and its effect on finance